First Record of the Superfamily Eurysquilloidea (Crustacea: Stomatopoda) from Japan - Hiroki Nakajima; Taigi Sato; Naoto Jimi (Species Diversity, 2024)
Here we report the discovery of a single specimen of the eurysquillid mantis shrimp, Manningia andamanensis Ghosh, 1975, from Okinawa Island, southwestern Japan. This specimen is the first member of the superfamily Eurysquilloidea to be recorded from Japanese waters, and is the second record ever for this species. This new record significantly extends the range of M. andamanensis from the North Andaman Islands northeastward to Japan. Live coloration for this species is revealed in detail for the first time.